Effect of the gintonin-enriched fraction on glucagon-like-protein-1 release - Lee, R.; Choi, S.-H.; Cho, H.-S.; Hwang, H.; Rhim, H.; Kim, H.-C.; Hwang, S.-H.; Nah, S.-Y. (Multidisciplinary Digital Publishing Institute (MDPI), 2021)
Ginseng-derived gintonin reportedly contains functional lysophosphatidic acids (LPAs) as LPA receptor ligands. The effect of the gintonin-enriched fraction (GEF) on in vitro and in vivo glucagon-like protein-1 (GLP-1) secretion, which is known to stimulate insulin secretion, via LPA receptor(s) remains unclear. Accordingly, we examined the effects of GEF on GLP-1 secretion using human enteroendocrine NCI-H716 cells. The expression of several of LPA receptor subtypes in NCIH716 cells using qPCR and Western blotting was examined. LPA receptor subtype expression was in the following order: LPA6 > LPA2 > LPA4 > LPA5 > LPA1 (qPCR), and LPA6 > LPA4 > LPA2 > LPA1 > LPA3 > LPA5 (Western blotting). GEF-stimulated GLP-1 secretion occurred in a dose-and time-dependent manner, which was suppressed by cAMP-Rp, a cAMP antagonist, but not by U73122, a phospholipase C inhibitor. Furthermore, silencing the human LPA6 receptor attenuated GEF-mediated GLP-1 secretion. In mice, low-dose GEF (50 mg/kg, peroral) increased serum GLP-1 levels; this effect was not blocked by Ki16425 co-treatment. Our findings indicate that GEF-induced GLP-1 secretion could be achieved via LPA6 receptor activation through the cAMP pathway. Hence, GEF-induced GLP secretion via LPA6 receptor regulation might be responsible for its beneficial effects on human endocrine physiology. ？ 2021 by the authors. Licensee MDPI, Basel, Switzerland.